Comparing Physical Attribute Distinctions in Male Kho-Kho Positions - Sarita Tyagi; Anil Kumar Vanaik; Monika Wasuja; Dessalegn Wase Mola (Physical Education Theory and Methodology)
Background. Kho-Kho, a traditional Indian sport, has separate roles for runners and chasers, each requiring unique physical attributes. Research on the specific physical and anthropometric characteristics of players in this position is limited, highlighting the need for this study to optimize performance at the national level.